1981
DOI: 10.1111/j.1432-1033.1981.tb06432.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Phosphatidylcholine‐Transfer Protein from Bovine Liver with Butanedione and Phenyiglyoxal

Abstract: Modification of arginine residues with 2,3‐butanedione and phenylglyoxal completely inhibits the transfer activity of the phosphatidylcholine transfer protein from bovine liver. Removal of borate and butanedione leads to a slow reactivation of the protein. Both α‐dicarbonyl reagents modify three of the ten arginine residues present per protein molecule. The extent of modification is linearly related to the loss of activity. Inactivation with butanedione is greatly diminished when the protein is bound to strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 40 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Some structural roles in the formation and stability of active conformation are suggested for this hydrophobic core of PBP, which contains no disulfide bonds. It has been shown that arginine residues have an important role in enzymes that act on phosphate-containing substrates (2,31,38). Among the four arginine residues of PBP, two consecutive arginine residues are localized at positions 109 and 110.…”
Section: Discussionmentioning
confidence: 99%
“…Some structural roles in the formation and stability of active conformation are suggested for this hydrophobic core of PBP, which contains no disulfide bonds. It has been shown that arginine residues have an important role in enzymes that act on phosphate-containing substrates (2,31,38). Among the four arginine residues of PBP, two consecutive arginine residues are localized at positions 109 and 110.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the number of j residues, many investigators have examined the effects of specific ligands on inactivation and modification of proteins [e.g. Akeroyd et al, 1981;Ramakrishna & Benjamin, 1981;Carrillo et al, 1981;Tso & Zalkin, 1981;Cromartie, 1981;Brooker & Slayman, 1983;Hennecke & Plapp, 1983; as well as the papers cited by Horiike & McCormick (1980) and Rakitzis (1984)]. In the absence and the presence of a ligand, the differences in both the nunmber of residues modified (m) and the fractional remaining activity (a), i.e.…”
Section: Bj-1 C Lettersmentioning
confidence: 99%
“…The cross-reactivity of bovine hFABP with corresponding proteins from rat and human liver has been considered already [4] and Northern blot analysis of bovine-hFABP mRNA was positive with synthetic oligonucleotides that were colinear with rat hFABP cDNA [32]. It is well known that essential Arg residues are found in proteins that act on phosphate-containing substrates [22, 33, 341, e. g. in phosphatidylcholine-transfer protein from bovine liver, one of the ten Arg residues interacts electrostatically with the polar head group of phosphatidylcholine [22]. We found no evidence that bovine hFABP binds this phospholipid [2, 111; however, the binding of lysophosphatidylcholine by rat hFABP was reported recently [35].…”
Section: Electrostatic Interactionsmentioning
confidence: 99%